Creation is Incarnation: The Metaphysical Peculiarity of the Logoi in Maximus Confessor. (7th September 2017) - Wood, Jordan Daniel
Abstract: Maximian logoi or the "principles" of created being are often virtually identified with Platonic ideas or forms. This assumption obscures what is distinctive about Maximus's concept of the logoi . I first note two metaphysical peculiarities of his doctrine, and then propose that these only make sense if we follow Maximus's own directive to read the logoi through Christology proper – that is, as describing creation as the Word's cosmic Incarnation. This suggests, in creative tension with a good deal of twentieth‐century philosophical theology, that the God‐world relation is not fully exhausted by the analogia entis : Maximus divines a still deeper hypostatic (not natural) identity between Word and world that actually generates natural difference – for perhaps the first and only time in the history of Christian thought. Here I assay a first step toward retrieving that relation.